Effectiveness Use Of Google Classroom Against Employee Classes As An Alternative Form Of Distance Learning: Effectiveness Use Of Google Classroom Against Employee Classes As An Alternative Form Of Distance Learning - Yunan Fauzi Wijaya (Jurnal Mantik, 2020)
The development of technology in education namely Blended learning adds convenience for students and lecturers in the learning process. This is because blended learning can be done online and remotely. Therefore blended learning is very useful for employee class students in the course process because the schedule of national university employee class meetings is not the same as a regular class. Blended learning becomes one of the alternative learning solutions for the employee class. The blended learning used in this study is Google classroom. Google Classroom is a learning app issued by Google that provides easy access through computers and mobile phones that are very useful for students and lecturers in the learning process. The purpose of this study is to describe blended learning, know google classes as an alternative to learning, and know the effectiveness of using google classroom against the class of employees. In this study, google classroom effective is expected in the process of distance learning students in the class of employees of National University